High stiffness polymer composite with tunable transparency. Issue 5 (June 2018) - Owuor, Peter Samora; Chaudhary, Varun; Woellner, Cristiano F.; Sharma, V; Ramanujan, R.V.; Stender, Anthony S.; Soto, Matias; Ozden, Sehmus; Barrera, Enrique V.; Vajtai, Robert; Galvão, Douglas S.; Lou, Jun; et al.
Graphical abstract: Abstract: Biological materials are multifunctional performing more than one function in a perfect synergy. These materials are built from fairly simple and limited components at ambient conditions. Such judicious designs have proven elusive for synthetic materials. Here, we demonstrate a multifunctional phase change ( pc ) composite from simple building blocks, which exhibits high stiffness and optical transmittance control. We show an increase of more than one order of magnitude in stiffness when we embed paraffin wax spheres into an elastomer matrix, polydimethylsiloxane (PDMS) in a dynamic compression test. High stiffness is mainly influenced by presence of microcrystals within the wax. We further show fast temperature-controlled optical switching of the composite for an unlimited number of cycles without any noticeable mechanical degradation. Through experimental and finite element method, we show high energy absorption capability of pc-composite . Based on these properties, the pc-composite could be used as an effective coating on glasses for cars and windows. This simple approach to multi-functionality is exciting and could pave way for designs of other multifunctional materials at the macro-scale.